Faktor-faktor yang Berhubungan dengan Terjadinya Gangguan Pendengaran pada Pilot Helikopter dan Casa - Nurfitriyana Nurfitriyana; July Ivone; Pramusinto Adhy (Universitas Kristen Maranatha, 2020)
Noise-Induced Hearing Loss (NIHL) is a hearing disorder caused by noise. Noise with the intensity of 85 decibels (dB)or higher may damage the corti hearing receptor. Pilot is one of the riskiest occupations due to frequent noise exposure from aircraft machine. This research aimed to identify the influence of aircraft noise levels on hearing disorder of both helicopter and casa pilots. This is observational analytical research with cross-sectional design, involving 30 helicopter pilots and 30 casa pilots. The diagnosis of hearing disorder was done using secondary data from medical records. The aircraft noise was measured by sound level meter, the other risk factors were observed with questionnaire. Data were analyzed by chi-square with ?=0,05. The results showed that aircraft noise (p=0,009; OR=4,929), duration of working period (p=0,026; OR=8,308), and flight hours (p=0,006; OR=3,222) were related with hearing disorder, but not age (p=0,093; OR=3,222). We concluded aircraft noise, duration of the working period, and flight hours are related to hearing disorder of the pilots. Keywords: hearing disorder; pilot; noise; noise-induced hearing loss